Anti-Helicobacter pylori activity and oxidative burst inhibition by the naphthoquinone 5-methoxy-3,4-dehydroxanthomegnin from Paepalanthus latipes - Kitagawa, Rodrigo Rezende; Bonacorsi, Cibele [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Vilegas, Wagner [UNESP]; Raddi, Maria Stella Gonçalves [UNESP] (Sociedade Brasileira de Farmacognosia, 2012)
Helicobacter pylori is a bacterium recognized as the major cause of chronic gastritis and peptic ulcers. Infection by H. pylori induces inflammatory responses and pathological changes in the gastric microenvironment. The host Keywords: immune cells (especially neutrophils) release inflammatory mediators and large 5-methoxy-3,4-dehydroxanthomegnin amounts of reactive oxygen species (ROS), which are associated with an increased Helicobacter pyloririsk of developing gastric cancer. In this study, we evaluated the anti-H. pylori and oxidative burst antioxidantactivitiesofa1,4-naphthoquinone-5-methoxy-3,4-dehydroxanthomegnin. Paepalanthus latipes The antimicrobial activity was assessed using a spectrophotometric microdilution technique, and antioxidant activity was assessed by noting the effect of 5-methoxy3,4-dehydroxanthomegnin on the neutrophil oxidative burst using luminol-and lucigenin-amplified chemiluminescence. The results showed that 5-methoxy-3,4dehydroxanthomegnin is a potent anti-H. pylori compound (MIC 64 µg/mL and MBC 128 µg/mL) and a strong antioxidant. 5-Methoxy-3,4-dehydroxanthomegnin decreased luminol- and lucigenin-amplified chemiluminescence, with ED50 values of 1.58±0.09 µg/mL and 5.4±0.15 µg/mL, respectively, reflecting an inhibitory effect on the oxidative burst. These results indicate that 5-methoxy-3,4-dehydroxanthomegnin is a promising compound for the prevention and treatment of diseases caused by H. pylori infection, such as gastritis, peptic ulceration, and gastric cancer, because reactive oxygen intermediates are involved in the pathogenesis of gastric mucosal injury induced by H. pylori infections.
Keywords: 5-methoxy-3,4-dehydroxanthomegnin; Helicobacter pylori; oxidative burst; Paepalanthus latipes